Relações socioespaciais no contexto das indústrias de calçados informais de Campina Grande-PB - Almeida, Maria do Socorro Nicolly Ribeiro de (2011)
The study of informal footwear industries in the city of Campina Grande-PB is related to the creation of productive structure in its spatial context, social and economic development. Then, the objectives in the present research were: to discuss the origin and evolution of the industrial sector in Campina Grande, specifically the footwear sector, to identify and map the micro and small informal footwear industries in this space and, finally, to study the informal industries and its dynamics in the socio structure of the city. Thus, it was tried to discuss the reality of socio-casual footwear industries in Campina Grande, through a survey of analyticaldescriptive, with quantitative and qualitative approach. Among the findings, it was noted that the informal industries investigated have archaic physical structure and operational and cheap labor with little or no professional qualification, seasonal production of shoes, a fact that leads people in the activity to instability related to generation work, a small representation when compared to formal industries. The review of the study may suggest that the informal arrangement Campinense footwear needs efficient and effective actions on the part of institutions that support the industry, and government incentives, so that they develop and become competitive, adequate the current capitalist model of production, governed, for example, by technological innovation and expanding consumer markets, otherwise they are bound to decrease and even disappear. Therefore, this work is proposed to contribute to a better knowledge about the origin of "sweatshops" of shoes, and to analyze the socioeconomic role of informal activity shoe for the city of Campina Grande.